Computer morphometry: experience in the study of clinical value in endometrial precancer - A. Kh. Bishtavi; O. A. Gornykh; A. A. Kanibolotsky; Yu. Yu. Tabakman; I. B. Manukhin (ABV-press, 2014)
The differential diagnosis of simple endometrial hyperplasia (SEH), complex endometrial hyperplasia (CEH), atypical endometrial hyper- plasia (AEH), and endometrial cancer (EC) is associated with a number of difficulties, frequently giving rise to different interpretations of the same histology specimens.Objective: to assess the possibilities of computed morphometry in endometrial hyperplasia.Subjects and methods. The investigation included 35 patients, including 12 with SEH, 11 with CEH, 7 with AEH, and 5 with EC. Endome- trial computed morphometry was performed using the ImageScope Color.Conclusion. The morphometric changes in endometrial hyperplasia, which are expressed in quantitative indicators, are much more diverse than their schematic image in the current classification, which may be a reason for a difference between the diagnoses.